2013
DOI: 10.1021/nn401667z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Tat Nanofibers as Effective Drug Carrier and Transporter

Abstract: Cell penetrating peptides (CPPs) have been extensively explored as molecular vectors through covalent linkage to anticancer drugs to improve the drug’s water solubility and to help overcome multidrug resistance. We report here the use of the Tat CPP as a molecular building unit to construct well-defined supramolecular nanofibers that can be utilized as a nanoscale vector to encapsulate the hydrophobic drug paclitaxel (PTX) (loading efficiency: 89.7 ± 5.0%) with a high loading capacity (6.8 ± 0.4%). Notably, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
143
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(146 citation statements)
references
References 85 publications
2
143
0
Order By: Relevance
“…16,17 At the same time, a category of self-assembling peptides as novel nanomaterials has emerged in the past decade with advanced properties in 18,19 Based on their chemical structures, selfassembling peptides could form different nanostructures including nanoparticles, nanotubes, and nanofibers, which are also potential carriers for drug delivery. [20][21][22][23][24][25][26] It has been demonstrated that nanostructures with a high aspect ratio are advantageous as drug carriers; 27,28 however, on the other hand, their drug loading capacity (LC) is usually very low, 24,29 which has hampered the development of a drug delivery system based on these nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 At the same time, a category of self-assembling peptides as novel nanomaterials has emerged in the past decade with advanced properties in 18,19 Based on their chemical structures, selfassembling peptides could form different nanostructures including nanoparticles, nanotubes, and nanofibers, which are also potential carriers for drug delivery. [20][21][22][23][24][25][26] It has been demonstrated that nanostructures with a high aspect ratio are advantageous as drug carriers; 27,28 however, on the other hand, their drug loading capacity (LC) is usually very low, 24,29 which has hampered the development of a drug delivery system based on these nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the localized drug-loaded nanofiber gel could promote immune suppression. 63 Zhang et al 64 utilized the self-assembling Tat peptide to encapsulate the hydrophobic drug paclitaxel to facilitate drug delivery and efficacy. First, four sequences with different numbers of hydrophobic tails were tested, and only the four-tailed sequence qC 8 -Tat self-assembled into nanotubes under aqueous solutions at a pH of 7.4 ( Figure 6).…”
Section: Applications In Medicine Drug Deliverymentioning
confidence: 99%
“…After the coumarin-6-loaded nanofibers were delivered into KB-3-1 cervical cancer cells, confocal microscopy indicated that hydrophobic drugs were transported into cancer cells at high efficacy through the adsorptive-mediated pathway. 64 For controlled drug releases, peptide hydrogels could encapsulate small molecules or proteins such as enzymes …”
Section: Applications In Medicine Drug Deliverymentioning
confidence: 99%
“…Amphiphilic peptides with distinct hydrophobic and hydrophilic segments can self-assemble into particular nanostructures in aqueous solutions (12). Peptide self-assemblies have been widely reported as nanocarriers to deliver antitumor drugs (13)(14)(15)(16)(17)(18). A peptide antagonist of CXCR4 was demonstrated to form self-assembled nanoparticles that exhibited innate activity against tumor metastasis (19).…”
Section: Improvement Of Stability and Efficacy Of C16y Therapeutic Pementioning
confidence: 99%